Insight into the mechanism and outcoupling enhancement of excimer-associated white light generation. Issue 6 (22nd February 2016) - Chen, Ying-Hsiao; Tang, Kuo-Chun; Chen, Yi-Ting; Shen, Jiun-Yi; Wu, Yu-Sin; Liu, Shih-Hung; Lee, Chun-Shu; Chen, Chang-Hsuan; Lai, Tzu-Yu; Tung, Shih-Huang; Jeng, Ru-Jong; Hung, Wen-Yi; et al.
Abstract : Fundamental insight into excimer formation ofCz 9 PhAn, achieving a single-component, high-performance WOLED. Abstract : Fundamental insight into excimer formation has been gained by using 9, 10-bis[4-(9-carbazolyl)phenyl]anthracene] (Cz 9 PhAn ) as a probe.Cz 9 PhAn exhibits a highly emissive blue fluorescence in solution and is found to emit a panchromatic white light spectrum (400–750 nm) in film, powder and single crystal, in which an additional excimer band appears at ∼550 nm. Detailed structural analyses, emission relaxation dynamics and a theoretical approach conclude the formation of an anthracene*/phenyl ring excimer through an overlap between π* (anthracene) and π (phenyl ring) orbitals in a face-to-edge stacking orientation. The rate of excimer formation is determined to be 2.2 × 10 9 s −1 at room temperature, which requires coupling with lattice motion with an activation energy of 0.44 kcal mol −1 . ExploitingCz 9 PhAn as a single emitter, a fluorescent white organic light emitting diode (WOLED) is fabricated with a maximum external quantum efficiency ( η ext ) of 3.6% at 1000 cd m −2 (4.2 V) and Commission Internationale de L'Eclairage (CIE) coordinates of (0.30, 0.33). The white-lightCz 9 PhAn reveals a preferred orientation of the transition dipole moment in the emitting layer to enhance light outcoupling. This non-doped, single component (Cz 9 PhAn ) WOLED greatly reduces the complexity of the fabrication process, rendering a green and cost-effective alternative among the contemporary display/lighting technologies.